PERAN PENYULUH AGAMA ISLAM NON PNS DALAM PROGRAM PEMBERDAYAAN MASYARAKAT TENTANG PEMAHAMAN AGAMA - Muhamad Syaifulloh; Andriyansah Andriyansah; Ansar Daud (LPSDI Bina Patria, 2023)
The Muslim community in the working area of ​​the Obaa District, Mappi Regency, Papua Province is not the majority population and there are still many Muslim communities who still lack religious understanding, therefore the role of Non-PNS Islamic Religious Counselors is very important and needed primarily in increase the understanding of Islam to the public. This study aims to determine the role of non-civil servant Islamic religious instructors in increasing religious understanding, especially among the Muslim community, as well as to determine the supporting and inhibiting factors in their implementation. Researchers used qualitative methods, namely field research, the subjects of this study were three informants and supported by library data and documentation and then drawing conclusions. The findings or conclusions of this study are that non-civil servant Islamic religious instructors play a role in increasing public religious understanding which are divided into three roles, namely: (1) Active role, by implementing informative, educative, consultative and advocate functions. (2) Participatory role, by participating in various religious activities. (3) Passive Role, where the extension agent becomes the source of the provider of facilities and infrastructure in the extension. The supporting factor is the collaboration between the extension worker and the Taklim Council group, while the inhibiting factor is the limited facilities and the lack of support from local government agencies